Building Big Profits in Real Estate: A Guide for The New Investor - Timmerson Wade (John Wiley, 2004)
Everyday, people just like you have a real chance to make serious money in real estate. All it requires is the discipline to purchase good property and the motivation to make new purchases that will create growing equity. Filled with in-depth insights and practical advice, Building Big Profits in Real Estate will show you the right way to invest in real estate.